Recent progress in the effect of ferroptosis of HSCs on the development of liver fibrosis - Tang, Rui; Luo, Jing; Zhu, Xiaoxia; Miao, Pengyu; Tang, Hong; Jian, Yue; Ruan, Sibei; Ling, Feng; Tang, Mingxi (Frontiers in Molecular Biosciences, 2023)
Fibrosis is a common pathological process that must take place for multiple chronic liver diseases to develop into cirrhosis and liver cancer. Liver fibrosis (LF) is regulated by various cytokines and signaling pathways in its occurrence and development. Ferroptosis is an important mode of cell death caused by iron-dependent oxidative damage and is regulated by iron metabolism and lipid peroxidation signaling pathways. In recent years, numerous studies have shown that ferroptosis is closely related to LF. As the main material secreted by the extracellular matrix, hepatic stellate cells (HSCs) are a general concern in the development of LF. Therefore, targeting HSC ferroptosis against LF is crucial. This review describes the current status of treating LF by inducing HSC ferroptosis that would aid studies in better understanding the current knowledge on ferroptosis in HSCs and the future research direction in this field.